Gerakan Aksi Nyata Program “Ayo, Tanam Seledri Sebagai Bentuk Pencegahan Hipertensi!” di Desa Kluncing, Licin, Banyuwangi - Nafkha Nisa Nabila; Septa Indra Puspikawati; Diansanto Prayoga; Avila Abilia; Firrial Eksa; Imelda Damayanti; Anggi Margareta; Putri Nur; Uyun Loveni; Melati Octavia; Lailatu Rohmah; Oktario Dinansa; Muhamad Isa; Fertika Nanda (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2024)
Hypertension is a significant health issue in Indonesia, with a growing prevalence. Some individuals still lack attention and support for hypertension prevention. The “Let's Plant Celery for Hypertension Prevention” movement in Kluncing Village aims to address this problem. The purpose of this program is to empower the community to plant celery as one of the plants that can prevent hypertension. The community service approach was employed, beginning with problem identification and priority determination, and concluding with program implementation. Socialization efforts were undertaken to educate the community about the benefits of celery and the process of planting it. Over 100 celery seedlings were distributed to the community and regularly monitored. Observations showed that celery growth reached its peak in the fifth week, with an average height of 4.39cm. During the sixth and seventh weeks, the celery continued to grow well, reaching an average height of 3.56cm and 3.39cm, respectively. By the end of the seventh week, the celery had reached maturity, with an average height of 27.20cm, indicating that the plant had fully matured. This program is a concrete step towards preventing hypertension and improving public health, with the active participation of the community. Sustainable practices in celery planting and consumption are expected to continue in Kluncing Village to obtain optimal health benefits in the prevention of hypertension.